CuHMMer: A load-balanced CPU-GPU cooperative bioinformatics application - Ping Yao; Hong An; Mu Xu; Gu Liu; Xiaoqiang Li; Yaobin Wang; Wenting Han (2010 International Conference on High Performance Computing and Simulation, 2010)
GPUs have recently been used to accelerate data-parallel applications for they provide easier programmability and increased generality while maintaining the tremendous memory bandwidth and computational power. Most of those applications use CPU as a controller who decides when GPUs run the computing-intensive tasks. This CPU-control-GPU-compute pattern wastes much of CPU's computational power. In this paper, we present a new CPU-GPU cooperative pattern for bioinformatics applications which can use both of CPU and GPU to compute. This pattern includes two parts: 1) the load-balanced data structure which manages data to keep the computational efficiency of GPU high enough when the length distribution of sequences in a sequence database is very uneven; 2) multi-threaded code partition which schedules computing on CPU and GPU in a cooperative way. Using this pattern, we develop CuHMMer based on HMMER which is one of the most important algorithms in bioinformatics. The experimental result demonstrates that CuHMMer get 13x to 45x speed up over available CPU implementations and could also outperform the traditional CUDA implementations which use CPU-control-GPU-compute pattern.